2023
DOI: 10.1108/jiabr-04-2022-0104
|View full text |Cite
|
Sign up to set email alerts
|

Alms tax (ZAKAT) compliance intention among entrepreneurs from a social cognitive perspective: the moderating role of knowledge

Abstract: Purpose This research aims to explore the moderating role of alms tax (zakat) knowledge in the relationship between extrinsic and intrinsic motivations (i.e. political instability, trust in institutions and service quality) and zakat compliance among businessmen in a Muslim developing country. Design/methodology/approach A final sample of 315 Algerian entrepreneurs randomly collected through a self-administered survey was analysed. Drawing on the social cognitive theory, estimation and analysis were done usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…According to Purwanto et al (2022) and Yusfiarto et al (2023), PBC is a customer's assessment of the ease or difficulty of using Islamic banking products. A previous study shows a positive and significant association between PBC factors and behavioural intents and compliance behaviour (Sadallah et al, 2023). Alzadjal et al (2021) found that Islamic bank clients' behaviour is highly influenced by their perception of behavioural control.…”
Section: Eligibilitymentioning
confidence: 91%
See 1 more Smart Citation
“…According to Purwanto et al (2022) and Yusfiarto et al (2023), PBC is a customer's assessment of the ease or difficulty of using Islamic banking products. A previous study shows a positive and significant association between PBC factors and behavioural intents and compliance behaviour (Sadallah et al, 2023). Alzadjal et al (2021) found that Islamic bank clients' behaviour is highly influenced by their perception of behavioural control.…”
Section: Eligibilitymentioning
confidence: 91%
“…Saad et al (2023) found a model to increase zakat compliance as income increased. Sadallah et al (2023) found that knowledge and political instability significantly affected businessmen’s zakat compliance, while service quality and trust had no significant effect on businessmen’s zakat compliance. Hoque (2023) examined Sharia compliance in welfare-oriented projects in corporate social responsibility (CSR), whose funds are from Zakat .…”
Section: Introductionmentioning
confidence: 90%